2001
DOI: 10.2460/javma.2001.219.765
|View full text |Cite
|
Sign up to set email alerts
|

Serum total thyroxine, total triiodothyronine, free thyroxine, and thyrotropin concentrations in dogs with nonthyroidal disease

Abstract: Results indicate that serum total T4, free T4, and total T3 concentrations may be low (ie, in the hypothyroid range) in dogs with moderate to severe nonthyroidal disease. Serum TSH concentrations are more likely to remain within the reference range in sick dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
160
6
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(199 citation statements)
references
References 16 publications
18
160
6
9
Order By: Relevance
“…20 In our study, FT4 levels were significantly lower before treatment than control group. FT4 levels were below normal values and TSH levels were normal or over normal limits in 35.7% of patients.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…20 In our study, FT4 levels were significantly lower before treatment than control group. FT4 levels were below normal values and TSH levels were normal or over normal limits in 35.7% of patients.…”
Section: Discussionmentioning
confidence: 66%
“…20,21 Kokei et al found normal FT4 and higher TSH levels in animals with non-thyroidal diseases. 22 In our study, secondary and subclinical hypothyroidism was determined in a significant portion of our patients (52%).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Decreased serum T 4 concentration has also been documented in humans with both anesthesia and surgery. 4,5,8,10,11,21 Severity of surgical trauma and postoperative complications are important determinants of alterations in serum T 4 concentrations, with decreased serum T 4 concentrations seen in patients undergoing cardiovascular surgery with cardiopulmonary bypass, 11,21 and in patients with more postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the euthyroid dogs with NTI was 6.2 years (range, 0.9-16.0 years); 16 dogs were female or spayed female and 19 were male or castrated male; and mean body weight was 34 kg (range, 22-48 kg). Clinical signs and abnormalities identified on physical examination included obesity (10 dogs), weakness (8), dermatitis (8), chronic otitis externa (8), lethargy (4), endocrine alopecia (3), stridor (3), hyperpigmentation (2), regurgitation (2), Horner's syndrome (2), seborrhea (1), and change in bark (1). Disorders included obesity (10 dogs), allergic dermatitis (flea, inhalant, or food; 8), weakness caused by neuropathy (8), otitis externa (8), cricopharyngeal dysmotility (4), laryngeal paralysis (3), and Horner's syndrome (2).…”
Section: Dogsmentioning
confidence: 99%